2015
DOI: 10.24123/aipj.v30i3.542
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment and Personality Traits and the Quality of Marriage of Husband and Wife Couples

Abstract: The study aimed to increase the quality of marriage by understanding the match between adult attachment and personality traits (which includes agreeableness, conscientiousness, and neuroticism) on marriage quality of couples. Five hundred couples or 1000 participants were recruited with cluster area sampling in five areas of Bandung City, and were asked to complete Marital Satisfaction Scale and Big Five Inventory. Data was analysed using Multiple Regression and Paired-Sample T-Test. Results showed that adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…From the results of research conducted by Florian (2002), it is concluded that adult attachment is a significant predictor of marital satisfaction. Secure adult attachments are positively correlated with marital satisfaction, and the adult attachment dimension plays a direct role in marriage quality (Fun-fun & Maria, 2015). Concluded that individuals with secure attachments with their partners consistently show higher levels of marital satisfaction than insecure ones (Hirschberger et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…From the results of research conducted by Florian (2002), it is concluded that adult attachment is a significant predictor of marital satisfaction. Secure adult attachments are positively correlated with marital satisfaction, and the adult attachment dimension plays a direct role in marriage quality (Fun-fun & Maria, 2015). Concluded that individuals with secure attachments with their partners consistently show higher levels of marital satisfaction than insecure ones (Hirschberger et al, 2009).…”
Section: Introductionmentioning
confidence: 93%